Kepuasan Pelanggan Dan Pemilihan Jasa Pendidikan - M. Munir (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2020)
Customer satisfaction is the estuary of the MMT business. The quality of the product / service needs to be improved to meet and even exceed customer satisfaction. Failure to meet customer / client satisfaction means failure to apply MMT. Other than that, educational institutions are part of a process of service to the community in accordance with the needs and challenges of the times. Meeting the needs of the community for the world of education is certainly very closely related to the satisfaction obtained by the community through existing education services. Customer satisfaction and selection of educational services can be described the results of the analysis that in educational institutions, customer satisfaction as in other product marketing activities. Customer satisfaction in education is very influential in the selection of these educational institutions. Although the educational services are not tangible, but customers can see and feel of it through the results of graduates and services provided by these educational institutions. Thus, customer satisfaction in the world of education greatly affects the quantity and selection of these educational institutions. Another thing that influences the selection of educational services, is inseparable from the marketing management of education carried out by the educational institution. Quality products are basically part of the indirect marketing of the educational institution, while indirect marketing is through the process of advertising, promotion and through product introduction activities of the educational institution, either in the form of achievements or activities. The conclusion of this discussion is that satisfaction with education services is closely related to the selection of education services. This is proven and implemented by the quantity and quality available in the educational institution.